MMDF Electronic Mail - Abaya, Efren F. (Philippine Engineering Journal, 2021)
E-mail is a system for sending electronic messages through a computer network. This paper discusses the internal processes of a mail system in a Unix and TCP/IP environment, focusing on the Multi-channel Memorandum Distribution Facility (MMDF).